Creative Media for Moral Drama: An Analysis of the Nine Virtues Reflected in the Vessantara Jataka - Fonramdee, Pusan; Bunyaphithak, Wassana; Pluempreecha , Jaroensek; Suksard , Weerakorn; Kaewkwang, Thanaphon (วิพิธพัฒนศิลป์, 2026)
This article the reflection of nine basic virtues as depicted in the Vessantara Jataka story, a revered Buddhist literary work known for its moral significance. The primary objective is to identify and analyze each of the nine virtues embodied within the story. We propose guidelines for applying these virtues through a moral drama, a creative medium intended to promote ethics and inspire audiences. For instance, the character of Chuchok serves as a catalyst for Dana Paramita (the perfection of giving), enabling Prince Vessantara’s acts of generosity to culminate in Bodhiñana (enlightenment knowledge). This journey ultimately leads to the highest level of perfection in his tenth life, achieving enlightenment in the realm of giving before his final birth as the Lord Buddha.